Near‐Infrared Photoinduced Coupling Reactions Assisted by Upconversion Nanoparticles. Issue 40 (25th August 2016) - Lederhose, Paul; Chen, Zhijun; Müller, Rouven; Blinco, James P.; Wu, Si; Barner‐Kowollik, Christopher
Abstract: We introduce nitrile imine‐mediated tetrazole–ene cycloadditions (NITEC) in the presence of upconversion nanoparticles (UCNPs) as a powerful covalent coupling tool. When a pyrene aryl tetrazole derivative ( λ abs, max =346 nm) and UCNPs are irradiated with near‐infrared light at 974 nm, rapid conversion of the tetrazole into a reactive nitrile imine occurs. In the presence of an electron‐deficient double bond, quantitative conversion into a pyrazoline cycloadduct is observed under ambient conditions. The combination of NITEC and UCNP technology is used for small‐molecule cycloadditions, polymer end‐group modification, and the formation of block copolymers from functional macromolecular precursors, constituting the first example of a NIR‐induced cycloaddition. To show the potential for in vivo applications, through‐tissue experiments with a biologically relevant biotin species were carried out. Quantitative cycloadditions and retention of the biological activity of the biotin units are possible at 974 nm irradiation. Abstract : Gently does it : The first example of upconversion photoinduced coupling chemistry based on the established tetrazole–ene cycloaddition system induced by near‐infrared light is introduced. The power of the technique, including tissue penetration, is demonstrated for small‐molecule ligation, macromolecular end‐group modification as well as polymer–polymer ligation.